Chelovek nedeli . Chelovek nedeli . Person of the Week . Человек недели - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with Arkady Kislitsin, a war veteran and mill owner. Contributors: Sarkisian, Elena (Anchor) Интервью с Аркадием Кислициным, участником войны, владельцем мельницы. Создатели: Саркисян, Елена (Ведущий/Ведущая)